The uric acid-to-HDL ratio as a predictive biomarker for depression risk in adult women - Wu, Yang; Wang, Zhe (Frontiers in Psychiatry, 2025)
BackgroundDepression disproportionately affects women, yet biomarkers for early risk stratification remain limited. This study examines the uric acid-to-HDL cholesterol ratio (UHR), a novel inflammatory and metabolic marker, as a potential predictor of depression in women.ObjectiveTo evaluate the association between UHR and depression risk in adult women.MethodsThis pooled cross-sectional analysis included 7,925 women aged ≥20 years, using the combined 2005–2018 NHANES cycles. Depression was defined by a Patient Health Questionnaire-9 (PHQ-9) score ≥10. UHR was calculated as uric acid (mg/dL) divided by HDL cholesterol (mg/dL) multiplied by 100%. Multivariable logistic regression was adjusted for sociodemographic, clinical, and lifestyle confounders. Threshold effects and subgroup analyses were conducted to explore nonlinear relationships and robustness across population strata.ResultsElevated UHR showed a linear association with increased depression risk. Each unit increase in UHR corresponded to a 5% higher likelihood of depression (OR=1.05, 95% CI=1.02–1.09). Women in the highest UHR quartile had nearly double the depression risk compared to the lowest quartile (OR=1.97, 95% CI=1.40–2.77). A critical inflection point at UHR=8.12 indicated a 6% incremental risk per unit beyond this threshold. Subgroup analyses confirmed consistent associations across demographic and clinical groups, with heightened effects in women aged <45 years.ConclusionHigher UHR levels are independently associated with depression in adult women, suggesting its utility as a metabolic-inflammatory biomarker for depression risk stratification. These findings highlight the interplay between lipid metabolism, oxidative stress, and mental health, advocating for UHR integration into preventive strategies for women’s mental well-being.